2020
DOI: 10.3390/antibiotics9080473
|View full text |Cite
|
Sign up to set email alerts
|

Country Income Is Only One of the Tiles: The Global Journey of Antimicrobial Resistance among Humans, Animals, and Environment

Abstract: Antimicrobial resistance (AMR) is one of the most complex global health challenges today: decades of overuse and misuse in human medicine, animal health, agriculture, and dispersion into the environment have produced the dire consequence of infections to become progressively untreatable. Infection control and prevention (IPC) procedures, the reduction of overuse, and the misuse of antimicrobials in human and veterinary medicine are the cornerstones required to prevent the spreading of resistant bacteria. Purif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 109 publications
(127 reference statements)
0
29
0
1
Order By: Relevance
“…Indeed, our results showed streptomycin and/or colistin resistant E. coli strains from different turkey organs. Antibiotic multiresistant bacteria are a serious threat to both animal and humans' health and difficult to cure as they resist commonly used antibiotics [ 42 ]. However, our experiments showed that gentamicin was effective against all the isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our results showed streptomycin and/or colistin resistant E. coli strains from different turkey organs. Antibiotic multiresistant bacteria are a serious threat to both animal and humans' health and difficult to cure as they resist commonly used antibiotics [ 42 ]. However, our experiments showed that gentamicin was effective against all the isolates.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of development of rhabdomyolysis and nephrotoxicity in neonatal foals treated with IV OTC for flexural deformity from now on should be considered. In light of the novel information provided by the presented cases and the “One Health” concept introduced in the early 2000s, veterinarians should make more judicious use of antibiotics [ 40 ], especially off-label, and consider alternative therapies for the treatment of flexural limb deformities in neonatal foals. Mild congenital cases of metacarpophalangeal flexural deformity often self-correct.…”
Section: Resultsmentioning
confidence: 99%
“…The models we generated can help to develop a better understanding of the process through which Antimicrobial resistance is established by providing critically important environmental parameters. Ultimately, we may be able to alter some of these parameters in order to control the Antimicrobial resistance establishment as part of the One health concept (Pieri et al, 2020 ). One could also speculate that longitudinal data of well defined geographic regions risk profiles, as it will inevitably become available (Bengtsson-Palme et al, 2018 ), can be used to evaluate the effectiveness of the public policy decisions.…”
Section: Discussionmentioning
confidence: 99%